(untitled) (Quinto Sol, 2025)
The purpose of this article is to register the presence of carnival ensembles that impersonated Indians in the carnivals of Argentina between 1864 and 1950 and to compare their main characteristics in two different regions, the northwest and the Pampas. Although the aesthetics they put into play combined older local elements and others that came from the transnational culture, the ensembles from the northwest took up pre-Hispanic Andean traditions and connected their performances with processes of reaffirmation of indigenous and mestizo ethnicities. Such elements are not visible in the Pampas ensembles, which nevertheless used similar aesthetics. Despite their differences, the comparison between those of the northwest, more studied, and those of the Pampas, which until this work had not deserved scholarly attention, allows us to shed light on the meanings of the practices of both and their relation to the official narratives regarding the ethnic profile of the nation.